Tantangan dan Peluang Dakwah Hijau di Era Digital: Studi Kualitatif pada Komunitas Muslim - Aris Sarjito (Universitas Nasional, 2025)
Green da'wah is an Islamic preaching approach that emphasizes the importance of environmental conservation as part of the khalifah fil-ardh (vicegerency on earth) mandate. Amid the rapid advancement of the digital era, millennial Muslim communities have vast access and potential to convey ecological messages grounded in Islamic values. This study aims to explore the challenges and opportunities of green da'wah within the context of digital media, focusing on millennial Muslim communities. The research adopts a descriptive qualitative method using secondary data, including scholarly articles, NGO reports, digital documentation, and national surveys. The findings reveal that digital media facilitates the dissemination of eco-theological messages, yet faces challenges such as misinformation, limited environmental literacy, and the dominance of consumer-driven content. Conversely, opportunities arise through online community networks, creative social campaigns, and visually driven da'wah. The study recommends a more adaptive, collaborative, and context-sensitive da'wah strategy tailored to the characteristics of digital-native Muslim millennials. Keywords: digital generation; digital media; green da'wah; Islamic ecology; millennial Muslims